CPM scheduling for construction : best practices and guidelines (Project Management Institute, Inc., 2014)
This volume compiles the work coordinated by the Scheduling Excellence Initiative Committee (SEI) to improve standardization and provide best practice guidelines for scheduling processes in the construction industry. It serves as a guide for all schedulers and planners from entry level to senior schedulers, as well as non-schedulers in management roles. The book itself is laid out in a way that follows the phases of building a project schedule: from project planning to project definition and schedule design, to development, maintenance, and usage of the schedule.